ANALISIS TEKNO-EKONOMI DAN DESAIN PROSES PRODUKSI BIOSTIMULAN CAIR BERBASIS FERMENTASI LIMBAH CAIR INDUSTRI TAHU - Rista Rahmaniyah Yansi; Ashifa Rahmawati; Mulyana Mulyana; Arinta Agnie Dewantari (PENDIDIKAN SAINS DAN TEKNOLOGI, 2026)
The utilization of tofu industry wastewater as liquid biostimulant represents an innovative approach to reducing environmental pollution while simultaneously creating economic value. The production process was carried out through 14 days of anaerobic fermentation, using tofu wastewater as the primary raw material, with EM4, coconut water, and molasses added as supplementary nutrients. The laboratory results showed that the nutrient content in the liquid biostimulant was 0.28% Nitrogen (N), 87.7 ppm Phosphorus (P), and 463 ppm Potassium (K). The results indicate that the initial production cost of Rp 4,675.00 per liter can be reduced to Rp 3,173.00 following plant optimization with a monthly capacity of 6,000 liters. The economic analysis revealed a net profit of Rp 10,962,500.00 per month with a payback period of less than two months. Application trials of liquid biostimulant on mustard greens and spinach demonstrated enhanced growth compared to the control, as reflected in increased plant height and greener leaf coloration. Accordingly, converting tofu wastewater into liquid biostimulant is both technically and economically feasible, offering a sustainable waste management strategy as well as a profitable business opportunity.